2016
DOI: 10.7554/elife.20621
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite CelTOS targets the inner leaflet of cell membranes for pore-dependent disruption

Abstract: Apicomplexan parasites contain a conserved protein CelTOS that, in malaria parasites, is essential for traversal of cells within the mammalian host and arthropod vector. However, the molecular role of CelTOS is unknown because it lacks sequence similarity to proteins of known function. Here, we determined the crystal structure of CelTOS and discovered CelTOS resembles proteins that bind to and disrupt membranes. In contrast to known membrane disruptors, CelTOS has a distinct architecture, specifically binds ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 67 publications
0
94
0
Order By: Relevance
“…Lipid strip probed with PfCelTOS, followed by primary antibody to CelTOS and a secondary antibody conjugated with peroxidase for visualization. PfCelTOS specifically bound to phosphatidic acid (Jimah et al ., 2016). B. Lipid strip probed with primary antibody against His-tag and a secondary antibody conjugated with peroxidase for visualization.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Lipid strip probed with PfCelTOS, followed by primary antibody to CelTOS and a secondary antibody conjugated with peroxidase for visualization. PfCelTOS specifically bound to phosphatidic acid (Jimah et al ., 2016). B. Lipid strip probed with primary antibody against His-tag and a secondary antibody conjugated with peroxidase for visualization.…”
Section: Figurementioning
confidence: 99%
“…Examples of lipid-specific pore-formation include Plasmodium CelTOS that depends on phosphatidic acid for pore formation, and the cholesterol dependent cytolysins (Jimah et al ., 2016; Lukoyanova et al ., 2016). CelTOS (cell traversal protein for ookinetes and sporozoites) is a malaria parasite protein that disrupts host cell membranes by pore formation to enable the exit of parasites from invaded host cells during cell traversal (Kariu et al ., 2006; Jimah et al ., 2016). Cholesterol dependent cytolysins are a large class of pore-forming proteins, including virulence factors of gram positive bacteria such as pneumolysin and listeriolysin (Lukoyanova et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of this protocol revealed that CelTOS ( ce ll traversal protein for o okinetes and s porozoites) disrupts membranes containing phosphatidic acid. This insight suggests that CelTOS is secreted by malaria parasites within invaded host cells to disrupt the host cell membrane and enable the exit of parasites (Jimah et al , 2016). Finally, this assay can be readily applied to investigate the inhibition of CelTOS-mediated liposome disruption by small molecules, antibodies or peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Pore-formation can be identified and evaluated by examining the blockade of carboxyfluorescein release with dextran molecules that fit the pore. The methods described here were used to determine that the malaria vaccine candidate CelTOS and proapoptotic Bax disrupt liposomes by pore formation (Saito et al , 2000; Jimah et al , 2016). Since membrane lipid binding by a biomolecule precedes membrane disruption, we recommend the companion protocol: Jimah et al , 2017.…”
mentioning
confidence: 99%